Identification of structural DNA variations in human cell cultures after long-term passage - Pavlova, GV; Vergun, AA; Rybalkina, EY; Butovskaya, PR; Ryskov, AP (Cell cycle (Georgetown, Tex.), 2015)
Random amplified polymorphic DNA (RAPD) analysis was adapted for genomic identification of cell cultures and evaluation of DNA stability in cells of different origin at different culture passages. DNA stability was observed in cultures after no more than 5 passages. Adipose-derived stromal cells demonstrated increased DNA instability. RAPD fragments from different cell lines after different number of passages were cloned and sequenced. The chromosomal localization of these fragments was identified and single-nucleotide variations in RAPD fragments isolated from cell lines after 8-12 passages were revealed. Some of them had permanent localization, while most variations demonstrated random distribution and can be considered as de novo mutations.